2017
DOI: 10.1164/rccm.201607-1385oc
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Pulmonary Fibrosis: The Association between the Adaptive Multiple Features Method and Fibrosis Outcomes

Abstract: More extensive baseline visual and AMFM fibrosis (as measured by GGR densities) is independently associated with elevated hazard for disease progression. Postbaseline change in AMFM-measured and visually measured GGR densities are modestly correlated with change in FVC. AMFM-measured fibrosis is an automated adjunct to existing prognostic markers and may allow for study enrichment with subjects at increased disease progression risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 40 publications
1
73
0
1
Order By: Relevance
“…Further, addition of the HRCT pattern variable to a multivariable model including baseline age, baseline lung function, smoking status, and fibrosis extent resulted in improvement in the c-statistic, suggesting that knowledge of this variable improves model discrimination. The guidelines-based HRCT pattern is commonly referenced in HRCT reports, making it a readily available data point providing physicians and patients useful prognostic information beyond that encompassed by clinical variables 35 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, addition of the HRCT pattern variable to a multivariable model including baseline age, baseline lung function, smoking status, and fibrosis extent resulted in improvement in the c-statistic, suggesting that knowledge of this variable improves model discrimination. The guidelines-based HRCT pattern is commonly referenced in HRCT reports, making it a readily available data point providing physicians and patients useful prognostic information beyond that encompassed by clinical variables 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The extent of fibrotic HRCT features including overall fibrosis score, honeycombing, reticular pattern, and traction bronchiectasis have been associated with poor prognosis in IPF and other fibrotic idiopathic interstitial pneumonias (IIPs) 25 . In unselected patients with fibrotic IIP, a definite UIP HRCT pattern has been associated with significantly worse survival compared to possible or inconsistent with UIP patterns 6,7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While quantitative disease assessment in lung fibrosis has been around for some years, its application in monitoring disease in therapeutic trials has recently gained interest. One notable recent study in this field by SALISBURY et al [76] involved textural analysis of a cohort of IPF patients enrolled in a clinical therapeutic trial using a novel adaptive multiple features method (AMFM) at two time points. The investigators observed that AMFM-measured fibrosis was independently related to the risk of disease progression as judged by a number of clinical and physiological measures, including the composite gender-age-physiology (GAP) score (a score accounting concurrently for patient age, gender, FVC and DLCO, where a higher score is associated with increased risk of mortality) and smoking history.…”
Section: Quantitative Computed Tomographymentioning
confidence: 99%
“…and used to explore the association between the AMFM regional characterization of the lung and outcomes in IPF patients(46) (Figure 2). Among patients with IPF enrolled in clinical therapeutic trials, both visual and AMFM measurement of baseline extent of mixed ground glass and reticular (GGR) densities predicted subsequent disease progression (defined as composite death, hospitalization, or >10% FVC decline), independent of baseline age, gender, and FVC.…”
mentioning
confidence: 99%